A study on the prevalence of Miltenberger blood group (GP. Mur) of antigens and antibodies among blood donors and patients with different blood group in Hospital Universiti Sains Malaysia (HUSM) - Ramli, Muhammad Azrul Hafizi (Universiti Sains Malaysia, 2013)
The MNS system was the second blood group system discovered and at least 16 of the 46 antigens in the MNS system result from genetic recombination, producing a hybrid glycophorin. The Mi (III) phenotype of the Miltenberger subsystem (GP. Mur) is one of hybrid glycophorin produced by genetic recombination of MNS system. The incidence of this hybrid glycophorin was highest in the East Asian populations and the antibodies developed were immunogenic especially IgG type which can cause hemolytic transfusion reaction (HTR), hemolytic disease of newborn and fetal (HDNF) and hydrops fetalis. The aim of the study was to detect the prevalence of anti-Mur and anti- MUT among patients and GP. Mur antigen in blood donors (healthy individuals) with different blood group in Hospital Universiti Sains Malaysia (HUSM). Blood samples from 27,322 patients with different blood group were screened by standard serological method for the anti Mi (HI) antibody from September 2012 to March 2013 while 80 blood donors with different blood group were selected to detect GP. Mur phenotype by serological method. Fifty-seven percent of donors were Malay while others were Chinese. Anti-Mi (III) antibody were detected in 0.3 % of both antenatal and general patients. Out of 83 patients, 15.7 % were positive for anti-Mur/MUT antibodies while others were diagnosed as possible of other anti-Mi (HI) antibodies. Based on blood group, 18.2 % of patients from A blood group were positive for anti-Mur/MUT antibodies while 20.0 %, 8.7 % and 15.4 % were detected from B, O and AB blood group. For GP. Mur phenotype, 5.0 % of Malay blood donors were detected to have GP. Mur antigen while only 1.3 % was identified in Chinese blood donors. Only 5 % of Malay blood donors from each A and O blood group were GP. Mur positive while 10 % of Malay and 5 % of Chinese have GP. Mur antigen in AB blood group. Based on the findings that GP. Mur antigen were higher in Malay blood donors and with many reports of clinical problems associated with the anti-Mi (III) antibody, it is warranted that the GP Mur red cells be included in screening panels for group and screen procedures in our hospitals.